ORGANIZING INDEPENDENT LEARNING IN PHYSICS LESSONS BASED ON HANDOUT MATERIALS AND AN ALGORITHMIC APPROACH (Bulletin of Innovative Research, 2026)
The article analyzes effective methods and didactic principles for organizing students’ independent work in physics lessons. The research results indicate that systematic independent work - combining textbooks, experiments, handouts, and algorithmic approaches — significantly enhances students’ knowledge quality, logical thinking, creative approach, and learning motivation.